Microstructural evolution of Ag based braze and its effect on the tribological behavior using different brazing current . - Cheniti, Billel; Badi, Rida; Yahmi, Youcef; Bouzid, Maamache; Balko, Jan; Hvizdos, Pavol; Miroud, Djamel (University of Eloued جامعة الوادي, 2018)
In this work, the WC-Co carbide/braze/1020 steel brazed joints have been prepared, using Tungsten Inert Gas (TIG) process. The effect of brazing current on the microstructure evolution of the Ag-Cu-Zn braze has been practically investigated. The results indicated that the braze contained three different phases: Cu solid solution, Ag solid solution and Ag-Cu-Zn eutectic phase, where their fractions depend on the brazing current applied. The interdiffusion reactions between the braze phases and their effect on the wear resistance were studied. Moreover, the mechanical properties especially the hardness (HIT) and Young’s modulus (EIT) of each phase were evaluated by nano-indetation measurements. The tribology test using linear mode revealed that, the wear mechanism becomes adhesive with the increase of brazing current.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Ag braze, interdiffusion, Microstructure, mechanical properties, wear resistance.